Epoxy adhesive cured at room temperature and used at high temperature and preparation method thereof

By adjusting the composition and distribution formula of epoxy glue, using raw materials such as bisphenol A epoxy resin, amine curing agents, etc., combined with functional fillers and accelerators, the problem of existing epoxy glues being difficult to achieve room temperature curing, high temperature resistance and high mechanical properties at the same time, and achieving room temperature curing, high temperature use and excellent mechanical properties.

CN115948139BActive Publication Date: 2025-03-25ZHUZHOU SHILIN POLYMER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211072837.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-03-25
Estimated Expiration
2042-09-02

AI Technical Summary

Technical Problem

It is difficult for existing epoxy adhesives to meet the requirements of room temperature curing, high temperature resistance and high mechanical properties at the same time.

Method used

By adjusting the composition and distribution formula of epoxy glue, using raw materials such as bisphenol A epoxy resin, amine curing agent, silane coupling agent, etc., combined with functional fillers and accelerators, an epoxy glue used for curing at room temperature and high temperature is formed.

Benefits of technology

It has achieved room temperature curing, high temperature use, good thixotropy and seam filling capabilities, high bonding strength, and anodized oxidation tank liquid resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003829838390000101
    Figure BDA0003829838390000101
Patent Text Reader

Abstract

The present invention relates to the technical field of epoxy adhesives, in particular to the field of IPC C09J163, and more specifically to an epoxy adhesive cured at room temperature and used at high temperatures and a preparation method thereof. The epoxy adhesive is composed of a component A mainly composed of a plurality of epoxy resins and a component B mainly composed of an amine curing agent. When the weight ratio of the resin to the functional filler is 10:(1-2), the shear performance and toughness of the epoxy adhesive are improved, and the heat resistance can also be improved at the same time, and it can also be applied to construction in the vertical direction; when the weight ratio of the resin to the corrosion inhibitor is 10:(1-2), the epoxy adhesive has excellent high temperature resistance, and at the same time, the corrosion resistance of the epoxy adhesive is improved, and it can be applied to the repair of spot welding joints, grooves, holes and defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of epoxy adhesives, in particular to the field of IPC C09J163, and more specifically to an epoxy adhesive that is cured at room temperature and used at high temperatures and a preparation method thereof. Background Art

[0002] Epoxy resin adhesive is a kind of engineering adhesive made of epoxy resin base material, curing agent, diluent, accelerator and filler. Due to its good mechanical properties and excellent bonding performance, small curing shrinkage, good electrical properties and good stability, it has been widely used in the fields of home appliances, automobiles, water conservancy and transportation, electronic appliances and aerospace industries in recent decades.

[0003] CN202011281014.7 provides a two-component epoxy adhesive with high heat resistance and high peel strength that cures at room temperature. It is based on acrylic modified epoxy resin and uses polyamide as a curing agent. The adhesive has a planar tensile strength higher than 5MPa and has certain heat resistance and aging resistance. However, when the temperature exceeds 80°C, the performance of the epoxy adhesive begins to decay to a certain extent.

[0004] CN201310723847.8 provides a high temperature resistant flame retardant epoxy adhesive and a preparation method thereof, which adopts a two-component epoxy resin and a curing agent. The epoxy adhesive has the advantages of good high temperature toughness, bonding strength and flame retardant properties, but it needs to be cured at a higher temperature. Summary of the invention

[0005] Currently, epoxy adhesives on the market are difficult to achieve room temperature curing, high temperature resistance, and high mechanical properties at the same time. The present invention explores the synergistic effects between epoxy adhesive components, and then obtains an epoxy adhesive that is cured at room temperature and used at high temperatures and a preparation method by adjusting the formula. The epoxy adhesive has the characteristics of room temperature curing, high temperature use, good thixotropy, strong filling ability, high bonding strength, and resistance to anodizing tank liquid.

[0006] To achieve the above object, the present invention provides an epoxy adhesive that is cured at room temperature and used at high temperature, the epoxy adhesive comprising component A and component B;

[0007] The component A comprises the following raw materials by weight: 65-170 parts of resin; 0-30 parts of toughening agent; 1-10 parts of diluent; 1-6 parts of high temperature plastic powder; 1-10 parts of functional filler; 1-8 parts of auxiliary agent;

[0008] The resin includes: one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, multifunctional epoxy resin, aliphatic epoxy resin and hydantoin epoxy resin.

[0009] The B component includes the following raw materials by weight: 80-120 parts of amine curing agent; 10-30 parts of accelerator; 10-20 parts of silane coupling agent; 10-20 parts of corrosion inhibitor; 3-30 parts of filler;

[0010] The bisphenol A epoxy resin is selected to have an epoxy value between 0.2 and 0.5.

[0011] Preferably, the bisphenol A epoxy resin includes E51, E44, E42, and E20, wherein the numbers represent the average epoxy value.

[0012] More preferably, the bisphenol A epoxy resin includes E51 (purchased from Hebei Zhuozheng Rubber & Plastic Products Co., Ltd.) or E44 (purchased from Hebei Zhuozheng Rubber & Plastic Products Co., Ltd.) or a mixture of the two.

[0013] Preferably, the bisphenol F epoxy resin includes F51, NPEF-170, EPALLOY 8220, and EPALLOY8230.

[0014] More preferably, the bisphenol F epoxy resin includes F51 (purchased from Jinan Baijin Chemical Technology Co., Ltd.) or EPALLOY 8230 (purchased from Xiamen Aikema Chemical Co., Ltd.) or a mixture of the two.

[0015] Preferably, the phenolic epoxy resin is EPALLOY 8330 (Xiamen Aikema Chemical Co., Ltd.).

[0016] Preferably, the multifunctional epoxy resin includes EPALLOY 8330, AG80 resin, and AG90 resin.

[0017] More preferably, the multifunctional epoxy resin is AG80 (purchased from Green Union Jining Chemical Technology Co., Ltd., model: MF-4101).

[0018] Preferably, aliphatic epoxy resin, CY183, CY184, UVR6128, UVR6103

[0019] More preferably, the aliphatic epoxy resin is UVR6128 (purchased from Wuhan Nobiguo Biotechnology Co., Ltd., model: NBG).

[0020] Preferably, the viscosity of the hydantoin epoxy resin is 3000-8000 mPa.s.

[0021] Further preferably, the hyaluronic acid epoxy resin is produced by Hubei Tosoh Chemical Technology Co., Ltd., with a viscosity of 3000-5000 and an epoxy value of 0.70-0.74 ep / 100 g.

[0022] The toughening agent includes polyurethane modified epoxy resin or carboxyl-terminated liquid nitrile rubber or a mixture of the two.

[0023] Preferably, the toughening agent is a polyurethane modified epoxy resin produced by our company, model: SL3401.

[0024] The diluents include benzyl alcohol, butyl glycidyl ether, 1,4-butanediol diglycidyl ether, and phenyl glycidyl ether.

[0025] Preferably, the diluent is benzyl alcohol (CAS No.: 100-51-6).

[0026] High temperature plastic powders include polysulfone, polyimide, polypropylene, and polylactic acid.

[0027] Preferably, the high temperature plastic powder polysulfone is purchased from Shanghai Lianfan Plastic Chemical Co., Ltd., model: P-1700.

[0028] Functional fillers include alumina, zinc oxide, magnesium oxide, zirconium oxide, silica, mica powder, kaolin, talc, bentonite, titanium dioxide, and white carbon black.

[0029] Preferably, the functional filler is talcum powder (purchased from Lingshou County Qiangdong Mineral Products Processing Plant, mesh number 1250 mesh), white carbon black (purchased from Yichang Huifu Nano Co., Ltd., HL-200), magnesium oxide (purchased from Xinshun Chemical, model MF-1000), and bentonite (purchased from Sishui County Hengjian Bentonite Co., Ltd., mesh number 320 mesh).

[0030] Additives include carbon black, red iron oxide, aluminum powder and copper powder.

[0031] Preferably, the auxiliary agent is red iron oxide, purchased from Lingshou County Shifeng Mining Processing Plant, with a mesh size of 325 mesh; aluminum powder, purchased from Changsha Xinkang New Materials Co., Ltd., with a mesh size of 300 mesh.

[0032] Amine curing agents include diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, and diaminodiphenyl sulfone.

[0033] The preferred amine curing agent is one or more of diethylenetriamine (CAS No.: 111-40-0), diaminodiphenyl sulfone (CAS No.: 80-08-0), and triethylenetetramine (CAS No.: 112-24-3).

[0034] The corrosion inhibitors include benzotriazole (CAS: 95-14-7), methylbenzotriazole (CAS: 29385-43-1), mercaptobenzothiazole (CAS: 29385-43-1), and 8-hydroxyquinoline copper (CAS No.: 10380-28-6).

[0035] Preferably, the corrosion inhibitor is 8-hydroxyquinoline copper (CAS No.: 10380-28-6).

[0036] The accelerator includes methyltetrahydrophthalic anhydride (CAS No.: 11070-44-3), dimethylbenzylamine, and 2,4,6-tris(dimethylaminomethyl)phenol.

[0037] Preferably, the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol (CAS No.: 90-72-2).

[0038] The silane coupling agent includes one or more of γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltrimethoxysilane.

[0039] More preferably, the alkane coupling agent is γ-aminopropyltriethoxysilane (CAS: 919-30-2) or γ-aminopropyltrimethoxysilane (CAS No.: 13822-56-5) or a mixture of the two.

[0040] Fillers include alumina, zinc oxide, magnesium oxide, zirconium oxide, silicon dioxide, mica powder, and kaolin.

[0041] Preferably, the filler is zinc oxide (CAS No.: 1314-13-2); mica powder, mesh size 300, purchased from Lingshou County Baiyi Mineral Products Processing Plant; magnesium oxide (purchased from Xinshun Chemical, model MF-1000).

[0042] When the weight ratio of resin to toughening agent is 20:(3-5), the epoxy adhesive achieves excellent heat resistance and also has good mechanical properties. As the proportion of resin in the epoxy adhesive increases, the crosslinking density of the epoxy adhesive increases, the distance between the molecular crosslinking points in the system becomes shorter, and the number of heat-resistant rigid groups (aromatic rings, aliphatic rings, etc.) on the molecular chain increases, thereby making its heat resistance better. However, at the same time, the high crosslinking density leads to high internal stress, which reduces the shear strength of the epoxy adhesive. By adding a large molecular long-chain toughening agent, the flexible chains can be cross-distributed in the epoxy crosslinking network, enhancing the movement of the chain segments and releasing the internal stress. When a large amount of toughening agent is added, the excessive flexibility of the chain segments will cause the thermal deformation temperature of the epoxy adhesive to decrease, thereby affecting the high-temperature performance of the epoxy adhesive. Furthermore, the applicant found that the toughening effect is better when polyurethane-modified epoxy resin is used as a toughening agent. It is speculated that the polyurethane-modified epoxy resin has a similar curing rate to the system, and phase separation is not easy to occur during the curing process, forming a uniform interpenetrating polymer network. The urethane groups in the polyurethane molecular chain are tough, impact-resistant, have strong adhesion and high peel strength, so that the epoxy adhesive has both mechanical properties and high-temperature properties.

[0043] Preferably, the weight ratio of resin to toughening agent is 20:(3-5).

[0044] More preferably, the weight ratio of the resin to the toughening agent is 20:4.

[0045] When the weight ratio of resin to functional filler is 10:(1-2), the shear performance and toughness of epoxy adhesive are improved, and the heat resistance can also be improved at the same time. It can also be used for vertical construction. Adding an appropriate amount of functional filler in the system prevents the molecular chain from slipping, improves the shear performance of epoxy adhesive, reduces the thermal expansion coefficient and curing shrinkage of the cured product, and reduces internal stress. When cracks appear due to overload, the functional filler can also prevent the cracks from expanding, thereby improving the bonding strength. However, too much filler will lead to uneven dispersion and affect the performance of epoxy glue. Further research has found that when the filler mesh is about 1000 mesh and talcum powder and white carbon black are used in combination, the effect is better. White carbon black is nano-shaped. It is speculated that silicon atoms and some groups in the epoxy resin matrix form heat-resistant weak chemical bonds at high temperatures, which improves the heat resistance of epoxy glue to a certain extent. However, there are a large number of silanol groups on the surface of white carbon black, which makes white carbon black hydrophilic, with high surface energy and poor affinity with non-polar molecular chains. Talc is a flaky structure with good compatibility with the system, and can load part of the nano-shaped white carbon black. At the same time, talcum powder has higher rigidity and can improve the mechanical properties of epoxy glue. Further research shows that white carbon black also plays the role of a thixotropic agent in the present invention. White carbon black forms thixotropy by forming a temporary structure in the epoxy glue system. When the system is not subject to shear force, or only under its own gravity, a network structure is formed by relying on intermolecular van der Waals forces, and the dispersion medium loses its flow characteristics in the network structure. When the thixotropic agent is added to the glue system, when the glue is stationary or not subjected to shear force, the viscosity of the system is increased, and the glue is provided with the ability to resist sag, so that it can stay on the vertical substrate surface. The epoxy glue has the application prospect of vertical construction.

[0046] Preferably, the weight ratio of the resin to the functional filler is 10:(1-2).

[0047] More preferably, the weight ratio of the resin to the functional filler is 10:1.5.

[0048] When the weight ratio of amine curing agent to accelerator is 20:(3-5), epoxy adhesive can be cured at room temperature and has excellent mechanical properties. After mixing, the AB components react to form a polyether cross-linked network. Due to the high reaction activation energy, the system usually requires a higher reaction temperature and a longer reaction time. Due to long-term heating, the benzene ring structure in the system is destroyed, and the epoxy adhesive aging phenomenon occurs. The addition of the accelerator plays a catalytic role, and its decomposition products can reduce the reaction activation energy of the curing agent, thereby reducing the reaction temperature and shortening the reaction time. As the content of the accelerator increases, the reaction activation energy of the epoxy resin during curing becomes lower. Under the same curing conditions, the more complete the curing degree of the epoxy resin, the greater the degree of cross-linking, and the higher the heat resistance of the epoxy adhesive. However, when the accelerator content is too high, the curing process will be too intense, which will further accelerate the curing rate and make the heat release more concentrated. Excessive temperature will cause the internal microstructure of the epoxy adhesive to be thermally oxidized and damaged, resulting in a decrease in mechanical properties. Further research found that when the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, the heat resistance of the epoxy adhesive is further improved. At the same time, the addition of hydroxyl groups is conducive to the generation of hydrogen bonds, which promotes the reaction between epoxy groups and amino groups and increases the room temperature curing rate of the epoxy adhesive.

[0049] Preferably, the weight ratio of the amine curing agent to the accelerator is 20:(3-5).

[0050] More preferably, the weight ratio of the amine curing agent to the accelerator is 20:4.

[0051] When the weight ratio of resin to corrosion inhibitor is 10:(1-2), the epoxy adhesive has excellent high temperature resistance and also improves the corrosion resistance of the epoxy adhesive, and can be used to repair spot welding surfaces, grooves, holes and defects. The corrosion inhibitor selected in the present invention has good compatibility with the system, and the small molecules of the corrosion inhibitor are evenly distributed in the cross-linked network, which plays a role in corrosion resistance. It is speculated that the corrosion inhibitor is released from the cross-linked network to the outer layer, adsorbed on the metal surface, and covered on the metal surface or the active site of the metal surface, changing the double electric layer structure of the metal in the medium, and increasing the activation energy of metal ionization, thereby inhibiting the electrochemical corrosion of the metal. The corrosion products produced during the corrosion process hinder the penetration of the corrosive medium, reduce the current density, and achieve the corrosion resistance effect. At the same time, it has a synergistic effect with the hydroxyl in the epoxy adhesive system and the SiO2 in the filler. The hydroxyl forms a -Si-OM (metal) covalent bond on the surface of the metal matrix. The -OH in the corrosion inhibitor forms Si-OH with SiO2 under hydrolysis conditions. The Si-OH molecules can condense into Si-O-Si chains to form a network structure film, which improves its bonding with the cross-linked network in the epoxy adhesive and further enhances the corrosion resistance of the epoxy adhesive. Further research found that when the corrosion inhibitor 8-hydroxyquinoline is added, the high temperature performance of the epoxy adhesive can be improved.

[0052] Preferably, the weight ratio of resin to corrosion inhibitor is 10:(1-2)

[0053] More preferably, the weight ratio of the resin to the corrosion inhibitor is 10:1.5.

[0054] When the weight ratio of resin to coupling agent is 10:(1-2), the high temperature performance of epoxy adhesive can be improved, and epoxy adhesive can be used in a high humidity environment. The addition of coupling agent can improve the interface between organic matter and inorganic filler in epoxy adhesive, enhance the compatibility of the system, and form a uniform cross-linked network after curing. If the amount of silane coupling agent is too much, the coupling agent will undergo cross-linking reaction after hydrolysis, thereby reducing the mechanical properties of the material. It was further found that the use of silane coupling agent KH550 can greatly improve the mechanical properties of epoxy adhesive. It may be that both KH550 and resin have epoxy groups, which further improves the compatibility with the system. KH550 plays a bridge role connecting the adhesive and the adherend at the bonding interface. After silane is hydrolyzed, silanol is generated. The silanol condenses and its head forms a hydrogen bond with the bonding surface, and the tail forms a chemical bond with the adhesive. The silane coupling agent forms a three-dimensional network cross-linked structure at the interface. When a branch chain breaks, the entire network structure can still connect the adhesive and the adherend, so the interfacial bonding strength is improved. At the same time, on the surface of the epoxy adhesive, the silanols generated after the hydrolysis of the silane coupling agent condense with each other to form a passivation film with a network structure, which covers the surface of the adhesive, and the water resistance of the epoxy adhesive is improved to a certain extent, making the epoxy adhesive in the present invention more suitable for long-term use in an environment with high humidity.

[0055] Preferably, the weight ratio of the resin to the coupling agent is 10:(1-2).

[0056] More preferably, the weight ratio of the resin to the coupling agent is 10:1.5.

[0057] The second aspect of the present invention provides a method for preparing an epoxy adhesive that is cured at room temperature and used at high temperature, comprising at least the following steps:

[0058] S1, the resin is added in 1-3 times, 1-3 resins are added each time; 1-4 resins are added, heated to 120-150°C, kept warm for 30-50min, mechanically stirred at 100-300r / min for 5-10min, high-temperature plastic powder is added, and mechanically stirred at 100-300r / min for 20-40min until the powder is completely dissolved by the resin, 1-3 resins are heated to 90-150°C, added to the mixed solution after dissolution, cooled to 60-80°C, 1-3 resins, diluent and toughening agent are added, mechanically stirred at 100-300r / min for 5-10min, functional fillers and additives are added, and mechanically stirred at 100-300r / min for 5-10min to obtain epoxy adhesive component A.

[0059] S2, the amine curing agent is added in 1-2 times, and 1-2 amine curing agents are added each time; 1-2 amine curing agents and accelerators are added, heated to 110-130°C and kept warm for 30-50min, mechanically stirred at 100-300r / min for 5-10min, 1-2 amine curing agents are added, mechanically stirred at 100-300r / min for 15-20min, cooled to 60-80°C, silane coupling agent, corrosion inhibitor and filler are added, and mechanically stirred at 100-300r / min for 5-10min to obtain epoxy adhesive component B.

[0060] Preferred:

[0061] S1, the resin is added in two times, 1-2 kinds of resins are added each time; after adding 1-2 kinds of resins, heating to 150°C, keeping warm for 40 minutes, mechanically stirring at 200r / min for 7 minutes, adding high-temperature plastic powder, mechanically stirring at 200r / min for 30 minutes until the powder is completely dissolved by the resin, heating 1-3 kinds of resins to 150°C, adding them to the mixed solution after dissolution, cooling to 60°C, adding 1-3 kinds of resins, diluents and toughening agents, mechanically stirring at 200r / min for 7 minutes, adding functional fillers and additives, and mechanically stirring at 200r / min for 7 minutes to obtain epoxy adhesive component A.

[0062] S2, the amine curing agent is added in 1-2 times, 1-2 amine curing agents are added each time; 1-2 amine curing agents and accelerators are added, heated to 120°C and kept warm for 40 minutes, mechanically stirred at 200r / min for 7 minutes, 1-2 amine curing agents are added, mechanically stirred at 200r / min for 15 minutes, cooled to 80°C, silane coupling agent, corrosion inhibitor and filler are added, and mechanically stirred at 200r / min for 7 minutes to obtain epoxy adhesive component B.

[0063] Beneficial effects:

[0064] 1. When the weight ratio of resin to toughening agent is 20:(3-5), the epoxy adhesive achieves excellent heat resistance and also has good mechanical properties.

[0065] 2. When the weight ratio of resin to functional filler is 10:(1-2):, the shear performance and toughness of the epoxy adhesive are improved, and the heat resistance can also be improved at the same time. It can also be used for vertical construction. Adding an appropriate amount of functional filler in the system can prevent the molecular chain from slipping, improve the shear performance of the epoxy adhesive, reduce the thermal expansion coefficient and curing shrinkage of the cured product, and reduce internal stress.

[0066] 3. When the weight ratio of amine curing agent to accelerator is 20:(3-5), the epoxy adhesive can be cured at room temperature and has excellent mechanical properties.

[0067] 4. When the weight ratio of resin to corrosion inhibitor is 10:(1-2), the epoxy adhesive has excellent high temperature resistance and also improves the corrosion resistance of the epoxy adhesive. It can be used to repair spot welding surfaces, grooves, holes and defects.

[0068] 5. When the weight ratio of resin to coupling agent is 10:(1-2), the high temperature performance of epoxy adhesive can be improved, and epoxy adhesive can be used in an environment with high humidity. DETAILED DESCRIPTION

[0069] Example 1

[0070] An epoxy adhesive that cures at room temperature and is used at high temperatures, the epoxy adhesive comprising component A and component B;

[0071] The component A includes the following raw materials by weight: 101 parts of resin, 20 parts of toughening agent, 5 parts of diluent; 3 parts of high temperature plastic powder, 12 parts of functional filler, and 0 parts of additive;

[0072] The resin includes: 80 parts of bisphenol A epoxy resin, 10 parts of bisphenol F epoxy resin, 0 parts of novolac epoxy resin, 0 parts of multifunctional epoxy resin, 3 parts of aliphatic epoxy resin, and 8 parts of hydantoin epoxy resin;

[0073] Component B includes the following raw materials: 100 parts of amine curing agent, 20 parts of accelerator, 15 parts of silane coupling agent, 20 parts of corrosion inhibitor, and 5 parts of filler;

[0074] The bisphenol A epoxy resin is E51, purchased from Hebei Zhuozheng Rubber & Plastic Products Co., Ltd.;

[0075] The bisphenol F epoxy resin is EPALLOY 8230, purchased from Xiamen Aikema Chemical Co., Ltd.

[0076] The aliphatic epoxy resin is UVR6128, purchased from Wuhan Nobiguo Biotechnology Co., Ltd., model: NBG;

[0077] The toughening agent is a polyurethane modified epoxy resin made by our company, model: SL3401;

[0078] The diluent is benzyl alcohol (CAS No.: 100-51-6);

[0079] The high temperature plastic powder is polysulfone, purchased from Shanghai Lianfan Plastics Co., Ltd., model: P-1700;

[0080] The functional filler is 10 parts of talcum powder, purchased from Lingshou County Qiangdong Mineral Products Processing Plant, mesh number 1250 mesh, and 2 parts of white carbon black (purchased from Yichang Huifu Nano Co., Ltd., HL-200);

[0081] The hydantoin epoxy resin is produced by Hubei Tosoh Chemical Technology Co., Ltd., with a viscosity of 3000-5000 and an epoxy value of 0.70-0.74 ep / 100 g;

[0082] The amine curing agent is 70 parts of triethylenetetramine (CAS No.: 111-40-0) and 30 parts of diaminodiphenyl sulfone (CAS No.: 80-08-0);

[0083] The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol (CAS No.: 90-72-2);

[0084] The alkane coupling agent is γ-aminopropyltriethoxysilane (CAS: 919-30-2);

[0085] The corrosion inhibitor is 8-hydroxyquinoline copper (CAS No.: 10380-28-6);

[0086] The filler is zinc oxide (CAS No.: 1314-13-2);

[0087] The method for preparing the epoxy adhesive that is cured at room temperature and used at high temperature comprises:

[0088] S1, add resin, heat to 150℃, keep warm for 40min, stir for 7min, add high temperature plastic powder, stir for 30min, cool to 60℃, add diluent and toughening agent, stir for 7min, add functional filler, stir for 7min to obtain component A.

[0089] S2, add amine curing agent and accelerator, heat to 120°C and keep warm for 40 minutes, stir for 7 minutes, cool to 80°C, add silane coupling agent, corrosion inhibitor and filler and stir for 7 minutes to obtain component B.

[0090] The stirring speed is 200 r / min.

[0091] Example 2

[0092] The specific implementation is the same as that of Example 1; the difference is that in Example 2:

[0093] The bisphenol A epoxy resin is E44 (purchased from Hebei Zhuozheng Rubber & Plastic Products Co., Ltd.);

[0094] The bisphenol F epoxy resin is F51, purchased from Jinan Baijin Chemical Technology Co., Ltd.;

[0095] The phenolic epoxy resin is EPALLOY 8330 (Xiamen Aikema Chemical Co., Ltd.);

[0096] The functional filler replaces talc with magnesium oxide (purchased from Xinshun Chemical, model MF-1000);

[0097] The auxiliary agent is 1 part of aluminum powder (purchased from Changsha Xinkang New Materials Co., Ltd., mesh number 300 mesh).

[0098] The amine curing agent is 70 parts of diethylenetriamine (CAS No.: 111-40-0) and 30 parts of diaminodiphenyl sulfone (CAS No.: 80-08-0);

[0099] The silane coupling agent is γ-aminopropyltrimethoxysilane (CAS No.: 13822-56-5);

[0100] The filler is silicon dioxide, purchased from Shandong Yinuo New Materials Co., Ltd., model: YN-2105;

[0101] The amount of toughening agent added is 0.

[0102] Example 3

[0103] The specific implementation method is the same as that of Example 2; except that the multifunctional epoxy resin in Example 3 is AG80 (purchased from Green Union Jining Chemical Technology Co., Ltd., model: MF-4101);

[0104] The functional filler is bentonite (purchased from Sishui County Hengjian Bentonite Co., Ltd., with a mesh size of 320 meshes);

[0105] The auxiliary agent is red iron oxide, purchased from Lingshou County Shifeng Mining Processing Plant, with a mesh size of 325;

[0106] The filler mica powder, mesh number 300, was purchased from Baiyi Mineral Products Processing Plant in Lingshou County;

[0107] Example 4

[0108] The specific implementation is the same as in Example 3; the difference is that in Example 4

[0109] The functional filler is 10 parts of magnesium oxide (purchased from Xinshun Chemical, model MF-1000); 2 parts of white carbon black (purchased from Yichang Huifu Nano Co., Ltd., HL-200);

[0110] The filler is magnesium oxide (purchased from Xinshun Chemical, model MF-1000);

[0111] Comparative Example 1

[0112] The specific implementation method is the same as Example 1; the difference is that the number of corrosion inhibitors added in Comparative Example 1 is 5;

[0113] The specific implementation method is the same as that of Example 1; the difference is that the number of accelerators in Comparative Example 2 is 5 parts;

[0114] Comparative Example 3

[0115] The specific implementation is the same as Example 1; the difference is that the number of parts of the toughening agent in Comparative Example 3 is 5 parts.

[0116] Comparative Example 4

[0117] The specific implementation is the same as Example 1; the difference is that the promoter in Comparative Example 4 is methyltetrahydrophthalic anhydride (CAS No.: 11070-44-3).

[0118] Performance Testing Methods

[0119] 1. According to the weight ratio of A:B of 4:1, the epoxy adhesive was mixed at 23±2℃, manually stirred or stirred with an electric stirrer at a speed of 100r / min for 5 minutes. The shear performance of the epoxy adhesive was tested at three temperatures of 23±2℃, 150±2℃ and 200±2℃ with reference to the standard GB / T7124-2008 "Determination of tensile shear strength of adhesives" (the substrate was LYl2CZ aluminum alloy, and it was cured at 23±2℃ for 48h).

[0120] 2. Resistance to anodizing solution, prepare test pieces according to standard GB / T 7124-2008;

[0121] a. Place the test piece in 100g / L NaOH solution and heat to 70±5℃, keep for 60 seconds, then rinse with tap water.

[0122] b. Place the cleaned test piece into 50% (volume ratio) nitric acid (ρ = 1.4, 23 ± 2°C), keep it for 30 seconds, then take it out and rinse it with tap water.

[0123] c. Place the cleaned specimen in step b into 200 g / L sulfuric acid (ρ = 1.84) at 23 ± 2 ° C for 40 minutes, then remove and rinse with tap water.

[0124] d. Put the cleaned test piece in 50g / L boiling potassium dichromate solution and boil for 20 minutes. Take it out and rinse it in tap water. Bake it in a 60-70℃ oven with air blowing for 2-3 hours. Turn off the oven and cool it to room temperature. Take it out and observe the adhesive layer. There should be no peeling, shedding, softening, bubbling, etc. Then test the shear strength according to GB / T 7124-2008.

[0125] 3. Heat aging: Prepare test pieces according to GB / T 7124-2008. Put the test pieces in a 150±2℃ oven. After 1000 hours, close the oven and let it cool for 24 hours. Then test the shear strength at 23±2℃ according to GB / T 7124-2008.

[0126] Performance test data

[0127]

Claims

1. An epoxy adhesive that cures at room temperature and is used at high temperatures, characterized in that: The epoxy adhesive consists of component A and component B; The component A comprises the following raw materials by weight: 65-170 parts of resin, 0-30 parts of toughening agent, 1-10 parts of diluent, 1-6 parts of high temperature plastic powder, and 1-10 parts of functional filler; The resin comprises: 80 parts of bisphenol A epoxy resin, 10 parts of bisphenol F epoxy resin, 3 parts of aliphatic epoxy resin, and 8 parts of hydantoin epoxy resin; The B component includes the following raw materials by weight: 80-120 parts of amine curing agent, 10-30 parts of accelerator, 10-20 parts of silane coupling agent, 10-20 parts of corrosion inhibitor, and 3-30 parts of filler; The toughening agent is polyurethane modified epoxy resin, the functional filler is talcum powder and white carbon black, the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol, and the corrosion inhibitor is 8-hydroxyquinoline copper; The weight ratio of the resin to the toughening agent is 20:(3-5); The weight ratio of the resin to the functional filler is 10:(1-2); The weight ratio of the amine curing agent to the accelerator is 20:(3-5); The weight ratio of the resin to the corrosion inhibitor is 10:(1-2).

2. The epoxy adhesive for room temperature curing and high temperature use according to claim 1, characterized in that: The weight ratio of the resin to the silane coupling agent is 10:(1-2).

3. The epoxy adhesive for room temperature curing and high temperature use according to claim 2, characterized in that: The amine curing agent includes one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine and diaminodiphenyl sulfone.

4. A method for preparing an epoxy adhesive that cures at room temperature and can be used at high temperatures according to any one of claims 1 to 3, characterized in that: The method for preparing the epoxy adhesive that is cured at room temperature and used at high temperature comprises: S1, add resin, heat to 120-150℃, keep warm for 30-50min, stir for 5-10min, add high temperature plastic powder, stir for 20-40min, cool to 60-80℃, add diluent and toughening agent, stir for 5-10min, add functional filler, stir for 5-10min to obtain component A; S2, add amine curing agent and accelerator, heat to 110-130℃ and keep warm for 30-50min, stir for 5-10min, cool to 60-80℃, add silane coupling agent, corrosion inhibitor and filler and stir for 5-10min to obtain component B.

Citation Information

Patent Citations

  • High-temperature resistant flame-retardant epoxy glue and preparation method thereof

    CN104726045A

  • Room-temperature-cured bi-component epoxy adhesive with high heat resistance and high peel strength

    CN112300740A

  • Room-temperature cured high heat-proof epoxy adhesive

    CN103897643A